THE Influence of Tiktok Social Media On Student Behavior At MTsN Nurul Huda - Nugroho, Wahyu Nugroho; Alhusna, Yulia; Tiyara, Tiyara; Thoha, Mahpudz (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This study aims to find out the impact on the TikTok application about student behavior at MTSN Nurul Huda. The type of research used is a quantitative type of research. The sample population numbered 87. The sample used in this study had 35 respondents using purposive sampling techniques. The theory used in this study is the CMC (computer-mediatedcommunication) theory. The data collection technique uses pearson product moment correlation by collecting data using a questionnaire or in the form of a questionnaire with 10 statement questions. So in the researchon student behavior that influences tiktok social media is with the statement of table 1, namely about the tiktok application that can help increase self-confidence, the results of 27 students agreeing and 8 students disagreeing. Table 2 positive and negative responses of users to the video made 33 sides agreed and 2 students disagreed. Table 3 issues of manners are declining due to the use of tiktok, 4 students agree 31 students disagree. Table 4 effect of tiktok downloads from friends and others, results 22 students agreed and 13 students disagreed. Table 4 objected to the withdrawal of tiktok permission by the Ministry of Communication and Information, 33 students agreed and 2 students disagreed. Table 6 doubts to re-download tiktok after its permission is allowed, 2 students agree and 33 students disagree, Table 7 becomes lazy after using tiktok, 13 students agree and 22 students disagree. Table 8 follows things that went viral on tiktok even though it was negative, 27 students agreed and 8 students disagreed. Table 9 not everyone likes tiktok 31 students agree and 4 students disagree. Table 10 became a better person after using tiktok, 30 students agreed and 5 sides disagreed.